ANALYSIS OF APPLICATION AND RESPONSIBILTY OF CSR BASED ON ISLAM AT BANK JATIM SHARIA (CASE STUDY AT BANK JATIM SHARIA) - Utami, Anis Dahniar (International Journal of Social Science and Business, 2017)
The concept of CSR aims to make a positive business activity with community activities so that no one is harmed from the existence of a company. So there must be awareness on the implementation of CSR is a shared responsibility to create harmony and harmony among stakeholders (Yusuf: 2010) CSR implementation in Indonesia is generally more applied by mining or manufacturing companies. But in its development, along with the global trend of CSR implementation, currently the company in the field of services such as banking has also presented aspects of social responsibility in the annual report. This is done not only by conventional banks but also by sharia banks. CSR turns out to be in harmony with the Islamic view of man in regard to himself and the social environment, can be presented with four axioms namely unity (tauhid), equilibrum, free will and responsibility. But in reality when we compare the concept of CSR in general, in addition to functioning as a value added for corporate image, CSR is budgeted and even become an annual program for the company. This research is expected to later be helpful when Bank Jatim Syariah has spin off. This research will also be able to provide information on the distribution and reporting process of CSR at Bank Jatim Syariah Keywords                        : CSR, CSR based On Islam, Islamic Bank, CSR Reporting, CSR Distributing